2015
DOI: 10.14720/aas.2014.103.2.15
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gamma radiation on seed germination of barley (Hordeum vulgare L.)

Abstract: The aim of the study was to determine the effect of gamma radiation on barley (Hordeum vulgare L.) seed germination and changes of seed viability associated with aging. The seed samples of the variety 'Astor' were irradiated at the Jožef Štefan Institute, in the Reactor Centre at Podgorica near Ljubljana, in 2006. The samples were irradiated with three different doses: 0.1, 0.2 and 0.4 kGy. After the irradiation, the seeds were stored in a refrigerator at 4 °C. The percentage of seed germination was tested eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
3
7
0
2
Order By: Relevance
“…Indeed, in the Variety EV8728, the germination rate is low only for the 200 and 300 Gy doses. Similar results have been reported by Rozman [9] and Neelamegam and Sutha [10]. According to the authors, irradiations may have no effect or may increase the rate of emergence.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, in the Variety EV8728, the germination rate is low only for the 200 and 300 Gy doses. Similar results have been reported by Rozman [9] and Neelamegam and Sutha [10]. According to the authors, irradiations may have no effect or may increase the rate of emergence.…”
Section: Discussionsupporting
confidence: 89%
“…This experiment presents that gamma irradiation might change the seedling morphological structure. Genetically, the low dosage of irradiation might alter the size of the chromosome, whereas, in high dose, there were chromosome failure and abnormal mitosis division (Bevilacqua and Vidakovic 400 Gy) and Hordeum vulgare (0.4 kGy) (Anbarasan et al 2013;Aparna et al 2013;Aynehb and Afsharinafar 2012;Harding et al 2012;Salve and More 2014;Rozman 2014;Songsri et al 2011). Meanwhile, Lokesha et al (1994) suggested that the inability of seeds to germinate due to high-dose irradiation might be caused to the changes in histology and cytology, interference and intrusion of the seed layer, and mitosis disruption or cell division removal in the meristematic zone during germination.…”
Section: Discussionmentioning
confidence: 99%
“…Rozman [21], realizó una investigación en cebada bajo condiciones contraladas y determinó diferencias estadísticas de germinación al utilizar una dosis de 400 Gy (70.5 %, a), mientras que los otros tres tratamientos (testigo, 100 y 200 Gy) no mostraron diferencias estadísticas (90.5%, b; 90.6%, b; y 86.8%, b, respectivamente), coincidiendo con los resultados encontrados en el presente estudio [21].…”
Section: A B Discusiónunclassified
“…Wang, Ma, Cao, Shan, & Jiao [23] en su estudio con la variedad de cebada de altura "Kunlun 15", irradiadas a diferentes dosis de rayos gamma (testigo, 50, 100, 150, 200, 250 y 300 Gy), indica que a medida que incrementa la dosis de irradiación disminuye la altura en plántula (testigo 14.3 cm; 300 Gy 7 cm), similares a los datos obtenidos en este estudio con la variedad INIAP Cañicapa (testigo 14.5 cm; 250 Gy 8.6 cm) [23]. Varias investigaciones mencionan que la variación en altura no solamente puede presentarse en una disminución del tamaño, sino también puede darse un incremento del crecimiento comparado con el testigo [20,21,24,25].…”
Section: A B Discusiónunclassified